2022
DOI: 10.3390/ijms23020804
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Burden and Immunomodulative Therapeutics of Cardiovascular Diseases

Abstract: Phenotyping cardiovascular illness and recognising heterogeneities within are pivotal in the contemporary era. Besides traditional risk factors, accumulated evidence suggested that a high inflammatory burden has emerged as a key characteristic modulating both the pathogenesis and progression of cardiovascular diseases, inclusive of atherosclerosis and myocardial infarction. To mechanistically elucidate the correlation, signalling pathways downstream to Toll-like receptors, nucleotide oligomerisation domain-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 87 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Although cardiac enzyme levels and infarct size by cardiac magnetic resonance imaging were significantly reduced (p=0.019), there was no reduction in adverse events. These results suggest a potential benefit of colchicine in AMI with ST -segment elevation (SLOBODNICK et al, 2018;TUCKER et al, 2021;KAO;HUANG, 2022).…”
Section: Colchicine In Acute and Chronic Coronary Syndromesmentioning
confidence: 68%
See 2 more Smart Citations
“…Although cardiac enzyme levels and infarct size by cardiac magnetic resonance imaging were significantly reduced (p=0.019), there was no reduction in adverse events. These results suggest a potential benefit of colchicine in AMI with ST -segment elevation (SLOBODNICK et al, 2018;TUCKER et al, 2021;KAO;HUANG, 2022).…”
Section: Colchicine In Acute and Chronic Coronary Syndromesmentioning
confidence: 68%
“…A retrospective study that evaluated 7,026 individuals after the intervention proposed that high levels of C-Reactive Protein (CRP) were correlated with all-cause mortality and the risk of AMI. A pioneering study demonstrated that colchicine can prevent elevation of biomarkers in an acute coronary event, as it suppressed the increase in IL-6 and CRP concentrations after coronary angioplasty (SHA et al, 2020;KAO;HUANG, 2022).…”
Section: Colchicine In the Vascular Inflammatory Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in this study, some traditionally considered risk genes and cell subsets of CAD patients did not enter our candidate team, such as CRP, MCP-1, monocytes, etc. We speculated that these patients might be related to statins or other therapeutic drugs, which have proved to be signi cantly changed the immune characteristics in peripheral blood [51].…”
Section: Animal Subject Validationmentioning
confidence: 99%
“…The inflammation/immunity-microbiota axis is also evaluated by the manuscript of Ting-Wei Kao focused on cardiovascular diseases [7]. An increased inflammatory status has recently been proposed as an independent risk factor for developing end-organ comorbidities and adverse prognoses of various chronic illnesses [8].…”
mentioning
confidence: 99%